2003
DOI: 10.1111/j.1365-2621.2003.tb05696.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Extraction from Heat‐stabilized Defatted Rice Bran: II. The Role of Amylase, Celluclast, and Viscozyme

Abstract: The effectiveness of 3 carbohydrases for protein extraction from heat-stabilized defatted rice bran (HDRB) was evaluated. Amylase, viscozyme and celluclast extracted a maximum of 45.4, 12.1, and 28.5% protein, respectively. Further study showed that extracted protein ranged from 9.5 to 58.4% under conditions of water to bran ratio (5:1 to 20:1), a-amylase (0 to 110000 units/10 g rice bran), temperature (35 to 55 °C), and time (1 to 8 h). The maximum protein extracted was 58.4% with a water to bran ratio of 17:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 14 publications
1
32
1
1
Order By: Relevance
“…These constitute nearly 20-24 %, 5-10 %, 1-2 % and 2-3 % of the total milled rice respectively. Rice bran contains high quality proteins and edible oil apart from fibre, ash and NFE (nitrogen free extract) and it is highly nutritious containing less cholesterol (Tang et al 2003;Mahanta, and Bhattacharya 2010). The presence of enzyme lipase is detected in rice bran which becomes active after milling.…”
Section: Introductionmentioning
confidence: 99%
“…These constitute nearly 20-24 %, 5-10 %, 1-2 % and 2-3 % of the total milled rice respectively. Rice bran contains high quality proteins and edible oil apart from fibre, ash and NFE (nitrogen free extract) and it is highly nutritious containing less cholesterol (Tang et al 2003;Mahanta, and Bhattacharya 2010). The presence of enzyme lipase is detected in rice bran which becomes active after milling.…”
Section: Introductionmentioning
confidence: 99%
“…By using a-amylase, protein extraction could be promoted by hydrolyzing a-1,4-glycosidic linkage to release starch bound proteins 7 . Tang et al 18 , also reported a potent ability of a-amylase to recover proteins from plant cellular matrix 13 . Considering Viscozyme-L, it is a cocktail enzyme consisting of arabinase, cellulase, β-glucosidase, hemicellulase, and xylanase, so it might effectively enhance protein liberation from the matrix 7,18 .…”
Section: Preparation and Characterization Of Rice Bran Proteinmentioning
confidence: 99%
“…Generally, EAI tended to increase with increasing DH suggesting improved emulsion formability of the more hydrolyzed peptides. This behavior could relate to developed S 0 and solubility at higher DH levels 5,18 . Increased S 0 enhanced protein adsorption on oil drop surfaces, resulting in improved EAI 5 .…”
Section: Effects Of Rice Bran Protein Hydrolysates On the Physicochemmentioning
confidence: 99%
See 2 more Smart Citations